Improving the Performance of Yogyakarta MSME Employees Through Strengthening Work Skills - Delta Annisa; R. S. Ismail (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting regional economic growth. However, efforts to improve employee performance are often constrained by limited work skills. This study aims to analyze the role of work skills enhancement in improving employee performance among MSMEs in Yogyakarta. The research employs a descriptive qualitative method, with data collected through interviews and observations involving MSME actors. The findings indicate that training, mentoring, and work habit development have a positive impact on employee productivity, discipline, and responsibility. The main obstacles identified include limited funding, time constraints, and a lack of external support. Overall, strengthening work skills has been proven to contribute significantly to improving employee performance within MSMEs in Yogyakarta.